A comprehensive overview of investments and human resource capacity in African agricultural research - Beintema, Nienke M.; Stads, Gert-Jan (International Food Policy Research Institute, 2017)
This report assesses trends in investments, human resource capacity, and outputs in agricultural research in SSA, excluding the private (for-profit) sector. The analysis uses information collected by Agricultural Science and Technology Indicators (ASTI)—led by the International Food Policy Research Institute (IFPRI) within the portfolio of the CGIAR Research Program on Policies, Institutions, and Markets (PIM). The comprehensive datasets were derived from primary surveys, collected through a series of consecutive data collection rounds; a small number of secondary sources, where survey data were missing or of poor quality; and ASTI’s older investment and human resource datasets. This report highlights the cross-cutting trends and challenges that emerged from the country-level data, structuring it within four broad areas: funding capacity, human resource capacity, research outputs, and institutional conditions—all in terms of whether they support or impede the effective and efficient conduct of agricultural research. This report concludes with a set of policy recommendations for regional and national-level decision makers, and other stakeholders.